Cross-sector partnership as a determinant of development – the perspective of public management - Wyrwa Joanna (Management, 2018)
Cross-sector partnership as a determinant of development - the perspective of public management Challenges faced by organizations in the area of public management today force them to seek new organizational forms to build a competitive advantage. In contemporary public management, two trends in particular can be observed. The first is to depart from repeatability and duplication of actions, and to follow instructions with a view to focusing on creativity and efficiency in solving problems. The second is to create partner relations not only within the public sector, but also in cooperation with organizations from other sectors. The article systematizes knowledge about cross-sector cooperation and is an attempt to organize research trends in this area. This paper is the result of literature research carried out in the form of systematic review of available sources - databases that aggregate scientific publications specific to this field. The article presents an integrated overview of cross-sector issues, allowing to establish the basis for future research.